Threat to the leatherback turtle - Hinman, Bonnie (Robbie reader. On the verge of extinction., 2009)
Describes the life and habitat of the leatherback turtle, the largest of the sea turtles, and focuses on the environmental efforts being taken in order to protect and preserve this endangered animal.